If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(0) = 15 + 3y Multiply 5 * 0 0 = 15 + 3y Anything times zero is zero. 0 = 15 + 3y Solving 0 = 15 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 0 + -3y = 15 + 3y + -3y Remove the zero: -3y = 15 + 3y + -3y Combine like terms: 3y + -3y = 0 -3y = 15 + 0 -3y = 15 Divide each side by '-3'. y = -5 Simplifying y = -5
| x+6=-5(x+6) | | 9a-18= | | 4*y-8=3*y+12 | | 10b-2=2b+14 | | 5+2m=6m+11 | | (10x+16)+54=90 | | 2(3x+5)+3=4x+7 | | 16000=650x-24000 | | 1y+2y= | | -7(4-5x)=-273 | | Y+20=4x | | -5(3-3x)+2x=-66 | | 3x+2(x+17)=149 | | -45=5s+20 | | 3(x-5)+1=4 | | -6a-6=-30 | | 40x^2-13x=3x^2+34x^2+5x | | 57+14x^2-12-13x-8x^2=5x+45 | | 23x-2=22x+1 | | 45x+60x*185y=10500 | | 3.6=0.6 | | 2-3*y=7*y+12 | | 3(-4+5g)=9g | | 0.66(2x-5)=0.75(x-2) | | 70=5g+3m | | 2a+5-5a= | | -72+9s=-81 | | 14x-7=10x+1 | | 3x-3=3+-3 | | 9*x+30=57 | | -10u+30=-10 | | 3x+37=9x-5 |